Structural transformations in solid and liquid n-butanol from FTIR spectroscopy. (22nd January 2020) - Doroshenko, I.; Vaskivskyi, Ye.; Chernolevska, Ye.
Abstract: FTIR spectra of n-butanol were registered for temperatures from −100 °С to 40 °С during heating of the sample and from 40 °С to −170 °С during its cooling. Structural changes at phase transitions solid–liquid and liquid–solid were detected. At n-butanol cooling below the melting point the initial crystalline structure was not achieved. Instead of it, a super-cooled liquid or amorphous phase was obtained. Quantum-chemical simulation of 27 n-butanol rotational conformers were provided via ROCBS-QB3 method. According to the calculations, the most stable conformer is TG′t. Comparison of calculated in the anharmonic approximation IR spectra of possible monomers and dimers of n-butanol with experimentally registered spectra showed that there are no monomers and dimers in the studied sample, and the structure of n-butanol in the condensed state is formed by bigger clusters.